Study on the Application of Green Practices in Supporting Sustainable Tourism at Shanti Restaurant North Jakarta - Japcilia, Eriska; Ardiansyah, Imam (Pusat Publikasi Nusantara, 2025)
This study aims to examine in depth the implementation of green practices at Shanti Restaurant in North Jakarta as an effort to support sustainable tourism. Utilizing a qualitative approach with a case study method, data were collected through observation, documentation, and in-depth interviews with two main informants: the Head Store and the Barista. The findings indicate that Shanti Restaurant has applied three primary dimensions of green practices: Green Action, Green Food, and Green Donation. In terms of Green Action, the restaurant manages organic waste through a composting system, reduces the use of single-use plastics, and repurposes non-organic waste such as used skewers into handcrafted decorations. Regarding Green Food, the restaurant sources organic ingredients from its own garden and local producers, and creates flexible menus based on seasonal availability and garden yields. Meanwhile, Green Donation is realized through environmental activities such as mangrove planting, participation in community-based environmental programs, and the dissemination of educational messages through visual media to foster environmental awareness. The study recommends strengthening partnerships with local suppliers to ensure sustainable sourcing, allocating modest CSR (Corporate Social Responsibility) funding for environmental initiatives, and expanding educational engagement with consumers to enhance the overall impact of sustainability practices.